Iš žodžių kilmės aiškinimų - Karaliūnas, Simas (Baltistica, 1978)
On the origin of some wordsLith. dial. apuokas “hair below, down” is said to be cognate either with Latv. apakša “bottom” (
Keywords: etimologija; lietuvių; latvių